Correlation between Parenting Style and Anxiety Levels in School-Age Children after Eruption of Mount Semeru at Huntara Lumajang - Nurhidayah, Ririn; Ira Rahmawati; Juliningrum, Peni Perdani; Sulistyorini, Lantin; Merina, Nuning Dwi; Rahmawati, Iis (KHD-Production, 2024)
Disasters are events that can threaten and become a disruption to life because they cause environmental damage, material loss, cause human casualties, and cause physical and psychological health problems. One of the psychological problems after a disaster is anxiety in vulnerable groups such as children. Apart from disaster factors, parenting style also influence children's anxiety levels. Parent with increased activity after the eruption causes children's basic needs to not be met, which becomes a post-eruption anxiety stressor. This research aims to determine the relationship of parenting style with anxiety levels in school-age children after the eruption of Mount Semeru in Huntara Lumajang. This research uses a cross sectional method. The sampling technique used non-probability sampling with a purposive sampling approach of 84 respondents. Data were collected using the PSDQ questionnaire for the variable parenting style and the Z-SAS questionnaire for the anxiety level variable for school-age children after the eruption. Test the correlation between parenting style and anxiety level in school-age children after the eruption using the contingency coefficient test. The results of the research show that there is a relationship between parenting style variable and the level of anxiety in school-age children after the eruption with p-value=0.002 (a=0.05). Once the correlation between variables is known, the nurse's role can be to take promotive and preventive actions to reduce and minimize anxiety problems in post-eruption children by paying attention to parenting style factors from parents.